PENGELOLAAN LINGKUNGAN BELAJAR DALAM MENINGKATKAN KUALITAS PEMBELAJARAN ANAK USIA DINI - Ampun Bantali; Haniva Nadillah; Dini Arianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of learning environments in improving the quality of early childhood education. The research is motivated by the importance of a conducive learning environment that supports children's cognitive, social, and emotional development. This study uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The results show that effective classroom arrangement, appropriate use of learning media, and positive teacher-child interactions significantly improve learning quality. A well-managed learning environment fosters active participation, creativity, and independence among children. Therefore, teachers play a crucial role in designing and managing learning environments to achieve optimal learning outcomes in early childhood education.